The therapeutic potential of glucagon-like peptide-1 for persons with addictions based on findings from preclinical and clinical studies - Elisabet Jerlhag (Frontiers Media S.A., 2023)
Although the multifaceted mechanisms underlying alcohol use disorder (AUD) have been partially defined, the neurobiological complexity of this disorder is yet to be unraveled. One of the systems that have gained attention in recent times is the gut-brain axis. Although numerous peptides participate in this axis, glucagon-like peptide-1 (GLP-1) plays a central role. GLP-1 is a crucial anorexigenic peptide, with potent abilities to reduce food intake and body weight. The physiological complexity of GLP-1 entails glucose homeostasis, gastrointestinal motility, and the release of insulin and glucagon. As reviewed in this study, acute or repeated treatment with GLP-1 receptor (GLP-1R) agonists decreases alcohol consumption in rodents. Moreover, the abilities of alcohol to promote hyperlocomotion, dopamine release in the nucleus accumbens, and reward in the conditioned place preference paradigm are all suppressed by GLP-1R ligands. Moreover, activation of GLP-1R suppresses the motivation to consume alcohol, alcohol-seeking behaviors, and relapse drinking in male rodents. Similarly, abstinence symptoms experienced during alcohol withdrawal are attenuated by activation of the GLP-1 pathway. On a similar note, the activation of GLP-1 receptors within areas of the brain that are processing reward modulates these alcohol-related responses. Another area that is crucial for this ability is the nucleus of the solitary tract, which is where GLP-1 is produced and from which GLP-1-containing neurons project to areas of reward. These findings may have clinical relevance as AUD is associated with polymorphisms in GLP-1-related genes. Although a GLP-1R agonist does not alter alcohol intake in AUD patients, it reduces this consumption in a sub-population of obese AUD individuals. Given the uncertainty of this outcome, additional clinical studies of obese AUD patients should explore the effects of the GLP-1R agonists on alcohol intake and body weight. Furthermore, GLP-1 receptors modulate the behavioral and neurochemical responses to addictive drugs. Taken together, these preclinical and clinical findings imply that the GLP-1 pathway plays a role in the complex mechanisms regulating alcohol and drug consumption patterns, unveiling a novel aspect of addiction medicine.